Efficacy and safety of panitumumab in a cohort of patients with metastatic colorectal cancer in France: PANI OUEST, a post–EMA-approval descriptive study with a geriatric oncology focus - Metges, Jean-Philippe; Douillard, Jean-Yves; Ramée, Jean-François; Dupuis, Olivier; Senellart, Helene; Porneuf, Marc; Deguiral, Philippe; Achour, Nach Eddine; Edeline, Julien; Cumin, Isabelle; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The Bretagne-Pays de la Loire cancer observatory, an oncology network created by the French Ministry of Health, is specifically dedicated to assess the use of new targeted anticancer therapies in routine practice. In line with the French National Cancer III program, our cancer network set up a real-life cohort, which is independent of the pharmaceutical industry, for patients with colorectal cancer to monitor patient safety and quality of care and promote pharmacovigilance. Materials and Methods: Panitumumab monotherapy was assessed in 243 patients with wild-type Kirsten rat sarcoma who were treated for metastatic colorectal cancer (mCRC) between July 2008 and December 2010 after prior chemotherapy using oxaliplatine and irinotecan. This was a post–European medicine agency marketing (EMA-M) study Results: This study shed light on the best practices, strategic adaptations, clinical results (treatment objective responses, 13%; progression free survival, 2.99 months [2.73-3.15]; and overall survival, 6.8 months [5.49-8.38]) as well as expected or unexpected (grade 3 or 4: 11.5%) secondary effects in the phase IV panitumumab treatment of mCRC. Conclusion: Our results are similar to those by Amado whose phase III study led to obtaining EMA-M for panitumumab and tend to confirm the antitumor activity of this antiepidermal growth factor receptor antibody in the treatment of mCRC. In addition, our results opened avenues to further assessment of panitumumab use as monotherapy as well as its benefit–risk ratio while taking into account the patients’ general and clinical characteristics. In 2012, the French National Authority for Health appended these data to the panitumumab transparency committee report.